The Effect of Adding MTMS (Methyl-trimethoxysilane) as a Pore Former on the Absorption of Hydrogels Based on NACMC (Sodium Carboximethyl Cellulose) - Dwi Anggraini; Prahady Susmanto; Ananda Aprilia; Delfiana Triaprilia Damayanti (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2026)
Superabsorbent hydrogels (SAHs) possess the remarkable ability to absorb and retain large amounts of water, making them promising eco-friendly materials for various applications. In this study, sodium carboxymethyl cellulose (NaCMC) was employed as the main polymer, modified with polyvinyl alcohol (PVA) to enhance structural stability through hydrogen bonding, and crosslinked with methyltrimethoxysilane (MTMS) to generate water-retaining porous networks. The effects of varying PVA and MTMS concentrations on the absorption capacity and chemical structure of the hydrogels were systematically investigated. The results demonstrated that the formulation containing 3 g of PVA and 4.71 mL of MTMS (B3) exhibited the highest absorption capacity of 453%, indicating optimal performance. These findings highlight the potential of NaCMC-based hydrogels as sustainable superabsorbent materials with promising applications in agriculture, water management, and biomedical fields.